CovidBChain: Framework for access‐control, authentication, and integrity of Covid‐19 data. (19th October 2022) - Pawar, Vijayant; Sachdeva, Shelly
Summary: In the Covid‐19 pandemic, information about the medical equipment such as personal protective equipment, ventilators, testing kits, oxygen cylinders, ICU beds, and patient diagnostic status is a black box for the patients. This article proposes a blockchain‐assisted Covid‐19 big data chain (CovidBChain) framework to handle the Covid‐19 data, which is of colossal size (volume), coming from different sources (variety) and generated at every time instance (velocity). CovidBChain is proposed to protect electronic health records and Covid‐19 equipment's information from illegal modification. CovidBChain provides transparency, access control, and integrity to Covid‐19 data. The status of critical equipment like ventilator, Covid‐19 beds, oxygen cylinder, and ICU status each such operation is integrated into the CovidBChain as a transaction. A prototype has been simulated using Ganache, Metamask, InterPlanetary File System, and Reactjs. The comparative assessment using proof‐of‐work (PoW) and proof‐of‐authority (PoA) deduces that the upload and retrieval time in PoA is less than PoW, while the transaction cost is more in PoW. The overhead of message exchange communication is reduced by a factor of 4 . 3 × 4.3× in PoA as compared to the PoW approach. CovidBChain has been tested on the Ethereum official test network Ropsten for PoW and Goerli for PoA.